Social Panorama of Latin America 1993 - United Nations (United Nations, 1993)
This second edition of the Social panorama of Latin America is an expression of the ECLAC secretariat's continuing efforts to incorporate the social dimension into the Commission's annual appraisals of regional development. The present report covers twice as many countries as the first, and the information has been updated using the most recent figures made available to the secretariat by the countries concerned; in addition, data for intervening years and for the latter part of the 1980s have been included.